Reproductive biology of Lutjanus guttatus (Perciformes: Lutjanidae) in Utría National Park, Colombian Pacific - Correa Herrera, Tatiana (2013)
Protected areas are important for natural population conservation since they work as refuge, feeding and breeding areas, where specimens should be exempt from human pressure. The generation of better criteria for management decisions and conservation of fishery resources, is based on the reproductive aspects of species that support fishing activities, since this information is related to the abundance, size and frequency of capture. With this aim, the reproductive biology of the spotted snapper Lutjanus guttatus was studied from April 2008 and February 2009 at the Utría National Park, Colombian Pacific. For this, we analyzed the volume of catch, size structure, sex ratio, fecundity, maturity size, breeding areas and seasons (n=278), of daily landings of 21 units of artisanal fisheries in ten fishing grounds in the Park. Form all landings, we evaluated a total of 4 319 individuals belonging to 84 species. Based on the number of individuals, Lutjanus guttatus ranked third in catches representing 6.4% (278 individuals), and 16th with 1.8% (95.79kg), based on catch biomass. The average weight was 0.34kg ±0.25kg, while 29cm±6.4cm for total length. The total length-weight relationship had the best fit (Kruskal-Wallis, p<0.05, n=272) with the equation PT=0.00000885* LT 3.09. The occurrence of mature fish and high condition factors suggested a spawning season in June, September and October in sandy and rocky shores. This species showed an asynchronical gonadal development, with a mean sexual maturity size estimated in 23.5cm total length, and an absolute fecundity of 156 253.11 oocytes (mode of 4μm diameter). We concluded that L. guttatus medium sizes observed indicated a fishing pressure on small size specimens (the minimum size being 18cm); thus, we recommend the implementation of minimum catch sizes based on the criterion of size at maturity LT100 (25.5cm) and to apply seasonal fishing closures during the highest reproductive activity (June- October). However, it is necessary to obtain additional biological information with multi-year monitoring to improve fisheries management criteria in the area.